OFR-4-81 Backfilling Of Cavities Produced In Borehole Mining Operations - M. H. Marvin (The National Institute for Occupational Safety and Health (NIOSH), 1979)
This report presents the results of a program to develop backfilling techniques to mitigate undesirable effects of hydraulic borehole uranium mining. Large underground cavities, formed during the borehole mining process, can be backfilled to prevent ground subsidence and to allow mining of adjacent uraniferous sandstone. Three backfilling techniques were tested in the laboratory and in the field: bulk dumping of slurry into the borehole from ground level, slurry injection under water, and slurry injection above the cavity water level. These techniques were tested with sand and with sand and one percent cement (by weight) mixtures. The project was accomplished in four tasks: equipment preparation and transport, mining operation to generate a full-sized cavity, backfilling operation, and assessment through core samples and subsidence checks. The concentrations of cement mixed with sand proved to be inadequate to bond the sand. Bulk dumping resulted in a 30-degree angle-of-repose, much too steep to completely fill the cavity. Both slurry injection techniques filled the cavity satisfactorily. However, underwater injection is the recommended backfilling technique because the borehole water level does not need to be pumped down during backfilling. The borehole itself was filled by bulk dumping of slurry. In conclusion, backfilling of borehole mining cavities is entirely feasible, and the preferred method is slurry injection under water.